Effects of Gegen Qinlian Decoction combined with Chinese herbal hot package on the expression of PCT, CRP and IL-6 in patients with acute gastroenteritis - Zhang, Weiwei; Yang, Mei; Rietz, Stephan; Li, Pei (Cellular and Molecular Biology, 2022)
This study was carried out to investigate the clinical efficacy of Gegen Qinlian Decoction combined with a Chinese herbal hot package in the treatment of acute gastroenteritis (AGE), and to analyze the effects on serum PCT, CRP and IL-6 levels. For this purpose, 100 patients with AGE admitted to the hospital from January 2019 to January 2022 were selected for the study and randomly divided into observation and control groups, with 50 cases in each group. Patients in the control group were given conventional Western medical treatment, while patients in the observation group were treated with Gegen Qinlian Decoction combined with a Chinese herbal hot package on this basis. The clinical efficacy, symptom relief time, main symptom scores and serum PCT, CRP and IL-6 levels before and after treatment were compared between the two groups. Results showed that the total effective rate of patients in the observation group was significantly higher than that in the control group (P<0.05). After treatment, the disappearance time of diarrhea, abdominal pain, fever and vomiting was significantly shorter in the observation group than in the control group (P<0.05). After treatment, the stool properties, number of stools and abdominal pain symptom scores of patients in both groups were lower than those before treatment, and the symptom scores of patients in the observation group were lower than those in the control group (P<0.05). The PCT, CRP and IL-6 levels of patients in both groups were significantly lower after treatment than before treatment, and the PCT, CRP and IL-6 levels of patients in the observation group were significantly lower than those in the control group (P<0.05). It was concluded that the clinical efficacy of Gegen Qinlian Decoction combined with Chinese herbal hot package in the treatment of AGE is remarkable, which can effectively improve the clinical symptoms and reduce the inflammatory reaction of patients and is worthy of clinical promotion.